Pembuatan Teknologi Tepat Guna Spinner Sebagai Alat Peniris Minyak Bawang Goreng - Girycki Sana Aleffin; Niniek Imaningsih; Cholid Fadil (Jurnal Ilmiah Wahana Pendidikan, 2023)
Shallots are one of Ngadiboyo Village's crops that support the lives of people who work as farmers. This crop is also the leading crop of the Rejoso sub-district, including Ngadiboyo village itself. Shallots are the main ingredient in fried shallot products. The fried shallot production business centered in Ngadiboyo Village has considerable potential for growth, if accompanied by the availability of abundant ingredients, a production process supported by the availability of adequate equipment, and an appropriate marketing strategy. This production activity continues to develop by facing various obstacles, one of which is in the packaging process where the packaged fried onions release residual frying oil, requiring Appropriate Technology (TTG) in the form of a Spinner or oil drainer. So the author and KKN-T Group 68 students from the National Development University "Veteran" of East Java, designed a tool to help Ngadiboyo MSMEs drain the oil in fried onions to improve quality. This tool assembly activity requires several tools and materials that are easily available and affordable.